Visual Storytelling and Micro-Influencer Collaboration: Driving Purchase Intent in Fashion E-commerce - Heru Tri Sutiono; Tugiyo Tugiyo; Sri Harjanti; Fitriana Ayu Eka Safina; Fajar Haryo Nimpuno (AIBPM Publisher, 2024)
This study aims to investigate the influence of visual storytelling and micro-influencers on fashion purchase intention among Generation Z in Indonesia. The research employed a quantitative approach, utilizing a self-administered online questionnaire. The findings of the study reveal that both visual storytelling and consumer engagement significantly impact purchase intention. Visual storytelling, particularly when engaging and relevant, positively influences consumer perception and, subsequently, purchase intent. However, consumer engagement emerges as a stronger predictor, emphasizing the importance of fostering interaction and community around the brand. While micro-influencers were expected to play a significant role, the results indicate a limited impact on purchase intention. This suggests that while micro-influencers can contribute to brand awareness and credibility, their influence may be less pronounced compared to other factors such as visual storytelling and consumer engagement. The study concludes by highlighting the importance of creating visually appealing and engaging content that fosters active consumer participation.